Arbuscular mycorrhizal fungi and biochar influence simazine decomposition and leaching. Issue 4 (26th January 2021) - Cheng, Hongguang; Wang, Jinyang; Tu, Chenglong; Lin, Shan; Xing, Dan; Hill, Paul; Chadwick, Dave; Jones, Davey L.
Abstract: The application of biochar to land has been promoted as a strategy for sequestering carbon in soils, for improving soil fertility and remediating soil pollution. However, the implications of biochar amendments on mycorrhizal associations and pesticide decomposition in agricultural soils are poorly understood. In this study, we compared the effects of four treatments; control (no biochar and no arbuscular mycorrhizal fungi (AMF), biochar (biochar without AMF), AMF (AMF without biochar) and biochar + AMF (AMF and biochar) on the fate of simazine. We specifically focused on the sorption, leaching and biodegradation behaviour of simazine. Our results showed that when symbiosis existed between plants and AMF, biochar inhibited simazine decomposition and AMF inoculation alleviated this inhibition. In contrast, this alleviation was not observed when the plant was removed. In addition, AMF inoculated into the biochar amended soil significantly decreased simazine concentration in the leachate; however, in the AMF‐only treatment, no effect on simazine leaching was observed. These phenomena were attributed to variation in the soil's sorption capacity due to biochar application or AMF inoculation. Overall, biochar application combined with AMF inoculation has the potential to mitigate simazine accumulation in the topsoil and reduce its availability. Abstract : The common effects of arbuscular mycorrhizal fungi (AMF) and Biochar on simazine fate. AMF mitigate the simazine accumulation in the soil due to biochar application. Biochar mitigate the competition between AMF with plant and other microbial.